Synthesis of pH-sensitive ternary hydrogel with synergetic antibacterial response for the release of ampicillin sodium - Andlib, Huma; Shafiq, Muhammad; Sabir, Aneela; Jabeen, Sehrish; Douglas, Timothy (Journal of Drug Delivery Science and Technology, 2025)
In the area of biomedicine, pH-responsive hydrogels have attracted a lot of attention. The smart novel polyelectrolyte complex carriers are made of chitosan, gum arabic and polyvinylpyrrolidone using various concentrations of ratan-jot plant extract for the release of sodium ampicillin antibiotic very first time. These hydrogels have been prepared by solution casting method and cross-linked by using 3-aminopropyldiethoxymethyl silane. According to swelling experiments, the cross linker concentration led to decreased swelling because the hydrogels were more tightly packed together. CPG-3A showed maximum swelling 54.5 g/g in 210 min. When the swelling behaviour of hydrogels was tested under various pH circumstances, it was found that they swelled most noticeably in alkaline media and least noticeably in acidic and neutral pH settings. These hydrogels may be appropriate for injection-based controlled drug release due to their unique pH-responsive behaviour. Ampicillin sodium salt was utilised as a model drug to analyse drug release behaviour of engineered hydrogel at pH 7.4. The results indicate that these smart hydrogels could be used for injectable controlled drug release (ampicillin sodium) for the treatment of wound as well as for other biomedical applications.
CRIS-Team Scopus Importer:2024-12-13
Keywords: Ampicillin sodium; Antibacterial response; Chitosan; Controlled release; Ratan-jot extract